Floristic Composition of Unda River Vegetation In Klungkung Regency, Bali - Wijana, I Made Sara; Wijaya, I Made Saka; As-syakur, Abd. Rahman; Indrawan, Gede Surya; Wiradana, Putu Angga; Swari, Komang Kartika Indi; Sari, Dewa Ayu Intan Tirta (Metamorfosa: Journal of Biological Sciences, 2022)
The downstream area of Unda River Watershed located in Klungkung Regency has experienced succession due to the eruption of Mount Agung in 1963. The ecosystem in the downstream area of the Unda River also experienced anthropogenic succession due to human activities which affected the plant species that composing the vegetation. This study aims to observe the floristic composition of vegetation in the downstream area of the Unda River. The research was conducted by exploration method in three types of ecosystems: lowland forest, marshes, and beaches. The results show the floristic composition in the downstream of Unda River composed by 163 plant species, classified in 48 families and 128 genera. The major growth form is small herb (47 species), grass (35 species), and tree (31 species). Fabaceae is the plant family with the most abundant species, followed by Poaceae and Cyperaceae. Based on the research zones, the lowland forest has the highest number of plant species (120 species), while the beach zone has the lowest (82 species). The ecosystem stability in the downstream area of Unda River can be disturbed by the existence of invasive species, such as Eichhornia crassipes , Chromolaena odorata , Lantana camara , Ipomoea carnea , Vachellia farnesiana , and Typha angustifolia .